An updated three-zone heat transfer model for slug flow boiling in microchannels. (May 2017) - Magnini, M.; Thome, J.R.
Highlights: A physics-based boiling heat transfer model for microchannel slug flow is proposed. The model estimates the time-dependent and time-averaged heat transfer coefficient. The latest findings about micro bubble dynamics and heat transfer are implemented. The influence of key flow parameters on heat transfer is clarified. The bubble frequency variation along the microchannel is investigated. Abstract: This work proposes a novel physics-based model for the fluid mechanics and heat transfer associated with slug flow boiling in horizontal circular microchannels to update the widely used three-zone model of Thome et al. (2004). The heat transfer model has a convective boiling nature and predicts the time-dependent variation of the local heat transfer coefficient during the cyclic passage of a liquid slug, an evaporating elongated bubble and a vapor plug. The capillary flow theory, extended to incorporate evaporation effects, is applied to estimate the bubble velocity along the channel. A liquid film thickness prediction method also considering bubble proximity effects, which may limit the radial extension of the film, is included. The minimum liquid film thickness at dryout is set to the channel wall roughness. Theoretical heat transfer models accounting for the thermal inertia of the liquid film and for the recirculating flow within the liquid slug are utilized. The heat transfer model is compared to experimental data taken from three independent studies. The 833 slug flow boiling data points cover the fluids R134a, R245fa and R236fa, and channel diameters below 1 mm. The proposed evaporation model predicts more than 80% of the database to within ±30%. It demonstrates a stronger contribution to heat transfer by the liquid slugs and correspondingly less by the thin film evaporation process compared to the original three-zone model. This model represents a new step towards a complete physics-based modelling of the bubble dynamics and heat transfer within microchannels under evaporating flow conditions.